Developing Responsibility, Ethics, And Strategic Planning: A Case Study On MSMEs In Mojokerto - Arif Isnaini; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Stone sculpture SMEs in Mojokerto is one of the creative economic sectors that has great potential in improving public welfare, especially in the Trowulan District and surrounding areas. However, challenges in business management, such as low operational responsibility, weak business ethics, and unstructured strategic planning, often become obstacles to business sustainability and competitiveness. This study aims to analyze the development of responsibility, ethics, and strategic planning at MSME patung batu in Mojokerto. The research method uses a qualitative approach to case studies with observation techniques, in-depth interviews, and documentation. The results showed that (1) strengthening responsibility can be done through a clear division of tasks and more disciplined production management, (2) business ethics need to be improved in aspects of honesty, price transparency, and marketing practices with integrity, and (3) strategic planning can be developed through SWOT analysis, determination of vision and mission, and product differentiation strategies. This research contributes to providing relevant management development models for local MSMEs.